Gender on the Scope of Written Text; in Persian and English Short Stories - Ferdows Aghagolzadeh; Abdollah Khosronejad (Teaching English Language, 2008)
This article is a field study that tries to verify the effect of gender on the scope of Persian and English written texts. Variables such as color terms, swearing, hedges, intensifiers, tag questions, adjectives of approximation and adjectives are considered for analysis in the study of selected literary texts in the corpus. The findings of this study show that in terms of color terms, both English and Persian female story writers use more color terms in their stories. Male writers are generally supposed to use more swearing in their stories. In terms of the use of hedging devices in the stories, it is shown that hedging expressions are found more frequently in female authored texts. The study of intensifiers (up graders, boosters) in Persian and English stories shows that, the use of intensifiers is more common within women’s writing style. In spite of the very infrequent use of tags in the stories, male authored texts provide more examples of tag questions. Challenging tags are more frequent in men's writing; female writers on the other hand prefer the use of epistemic tags. Frequency of the use of adjectives of approximation is not a good criterion to differentiate female authored texts from male authored ones in Persian corpus. On the other hand the use of this linguistic feature in English corpus demonstrates that female authored texts use these adjectives more frequently. The study of the use of adjectives in English and Persian corpus shows that female writers use adjectives more frequently in their writing.